Machining with carbides and oxides : a comprehensive work coverring the tool materials, machinability, planning, operations, and ecomics associated with modern metal removal - 7647 American Society of Tool and Manufacturing Engineers; Wilson, Frank W. (New York : McGraw-Hill, 1962)
20